2019
DOI: 10.1208/s12249-019-1564-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable Immune Response Induced by Intradermal DNA Vaccination by a Novel Needleless Pyro-Drive Jet Injector

Abstract: DNA vaccination can be applied to the treatment of various infectious diseases and cancers; however, technical difficulties have hindered the development of an effective delivery method. The efficacy of a DNA vaccine depends on optimal antigen expression by the injected plasmid DNA. The pyro-drive jet injector (PJI) is a novel system that allows for adjustment of injection depth and may, thus, provide a targeted delivery approach for various therapeutic or preventative compounds. Herein, we investigated its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 34 publications
(28 reference statements)
0
40
0
Order By: Relevance
“…A range of other devices have been developed and trialled in recent years. For instance, Genetronics Inc (San Diego, CA, USA) patented an injector pen, which uses a spring mechanism to apply needle-free intradermal injection of a liquid [ 176 ]. The Injex30 provided comparable antibody titres to subcutaneous N&S injection in a study with mice vaccinated against hepatitis B surface antigen [ 163 ].…”
Section: Vaccination Into the Dermal Compartment Without Needle Anmentioning
confidence: 99%
“…A range of other devices have been developed and trialled in recent years. For instance, Genetronics Inc (San Diego, CA, USA) patented an injector pen, which uses a spring mechanism to apply needle-free intradermal injection of a liquid [ 176 ]. The Injex30 provided comparable antibody titres to subcutaneous N&S injection in a study with mice vaccinated against hepatitis B surface antigen [ 163 ].…”
Section: Vaccination Into the Dermal Compartment Without Needle Anmentioning
confidence: 99%
“…Our previous studies have shown that the novel jet injector driven by explosives, called pyro-drive jet injector, was efficient for ID administration in rats and mice, leading to efficient expression of transgenes. 8 However, the immune response and the significance of pyro-drive jet injections following DNA vaccination in large animals seem to be unclear, as jet injectors adjusted for ID administration have not been used in the previous studies. In the present study, we evaluated the application of jet injection for gene transfer via ID injection compared with that of needle syringes, using pig skin as a morphological model that mimics human skin in a translational research.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The injection was efficient in promoting gene transfer, antigen expression, and immune responses in mouse and rat models. [5][6][7][8] However, although the studies using jet injection with small animals are promising, similar results are not always obtained in humans.…”
Section: Introductionmentioning
confidence: 99%
“…While publicly available information on the antigen and adjuvant is unavailable, it is evident that they are employing plasmid DNA delivered by a pyro-drive jet injector (PJI), which employs the detonation of small amounts of explosive powder to propel plasmids in a jet into the skin at variable, controllable depths [ 119 ]. In a preclinical evaluation of this technology to vaccinate against the model antigen ovalbumin in mice and rats, they demonstrated that plasmid DNA delivered by PJI induced significantly greater antigen expression and resultant antibody titers compared to needle-injected plasmid DNA [ 120 ]. This technology presents the advantage of needle-free, single step delivery with the potential to optimize the depth of delivery to induce the optimal immune response.…”
Section: Subunit Formulationsmentioning
confidence: 99%
“…Curevac has announced that they will begin Phase 1/2a clinical trials in June of 2020 for a SARS-CoV-2 vaccine, with this vaccine utilizing the same lipid formulation as Pfizer/BioNtech with mRNA encoding S protein of the virus [ 58 , 143 , 144 ]. This change from a protamine based carrier to a lipid based particle may be due to the fact that LNPs are shown to work better when given via standard intramuscular injection [ 145 ], whereas the protamine based formulation only induced neutralizing titers when administered with less common needle-free injection mechanisms similar to those used in previous studies of DNA vaccination [ 58 , 120 ]. Another consideration might be the enhanced storage they announced with their new LNP formulation, noting that they have a formulation suitable for storage at three months at standard refrigeration temperature (5 °C) [ 146 ].…”
Section: Subunit Formulationsmentioning
confidence: 99%